(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
Intrafamily violence when precocious, chronic and recurrent may lead to the development of mental disorders, including Posttraumatic Stress Disorder (PTSD) and Complex Trauma. The effects of exposure to intrafamily violence commonly are not limited to childhood and adolescence, and may impact psychological, social and occupational functioning in adulthood. The most effortful intervention to these cases involves individual psychotherapy (cognitive-behavioral psychotherapy) and family psychotherapy (systemic and cognitive-behavioral). In the cognitive-behavioral-systemic approach, the lifeline technique can be characterized as a useful strategy in the evaluation of the temporal course of the exposure to stressor events, as well as the adaptive and maladaptive answers from the members of the family system. The aim of this paper is to present a brief family psychotherapy process with a family exposed to multiple situations of intrafamily violence with the use of lifeline’s technique as a therapeutic approach.